The Role of Environmental Uncertainty, Firm Size, and Enterprise Risk Management to Improve Firm Performance - Maharani, Puan Putri; Pangestuti, Dewi Cahyani (Formosa Journal of Sustainable Research, 2024)
Global warming and other environmental problems are a major concern because related to corporate sustainability issues, so research is needed regarding various factors that influence company performance. This quantitative research was conducted to determine and analyze the influence of environmental uncertainty, firm size, and enterprise risk management on firm performance. The population in this study is the energy sector listed on Bursa Malaysia during 2017-2021. The sample selection used the purposive sampling method. Hypothesis testing using panel data regression with the E-Views 12. The results of this study show that, (1) environmental uncertainty has no effect on firm performance, (2) firm size has a positive effect on firm performance, (3) enterprise risk management has a positive effect on firm performance